Challenges in the health economics of familial hypercholesterolemia - Norman, Richard; Watts, G.; Weintraub, W.; Gidding, S. (Lippincott Williams & Wilkins, 2016)
Purpose of review: Implementation of effective interventions often requires evidence regarding value, that is, whether they are worth what we pay for them. This review explores recent evidence concerning cost-effectiveness in familial hypercholesterolemia, and discusses the cause of, and likelihood of solutions to, the paucity of such evidence. Recent findings: Cost-effectiveness analysis in familial hypercholesterolemia has been limited almost exclusively to adult populations. However, there is growing evidence that childhood intervention offers substantial benefit in terms of downstream health gains. Statin therapy in adults has been demonstrated to be cost-effective, but the range of novel agents that might be used will require de novo economic evaluation alongside exploration of their effect and safety profile. Summary: The familial hypercholesterolemia field has limited evidence regarding cost-effectiveness, which limits optimum allocation of resources. Economic evaluations are necessary to appraise new agents and optimal timing of management approaches. Evaluations often have substantial data demands; consequentially, their applicability to medical decision-making or policy will be partly determined by the availability of data, particularly those providing information about the long-term trajectory of health benefit from familial hypercholesterolemia treatment. Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved.